2021
DOI: 10.1101/2021.03.23.436678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mast cell function in prostate inflammation, fibrosis, and smooth muscle cell dysfunction

Abstract: Intraurethral inoculation of mice with uropathogenic E. coli (CP1) results in prostate inflammation, fibrosis, and urinary dysfunction, recapitulating some but not all of the pathognomonic clinical features associated with benign prostatic hyperplasia (BPH) and lower urinary tract symptoms (LUTS). In both patients with LUTS and in CP1-infected mice, we observed increased numbers and activation of mast cells and elevated levels of prostate fibrosis. Therapeutic inhibition of mast cells and the histamine 1 recep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Once again, these findings mirror the human disease, since elevated levels of CCL2 and CCL3, the Th1-associated chemokine CXCL10, mast cellderived tryptase and other mediators, and significantly increased effector Th1/Th17 cell proportions have been found elevated in expressed prostatic secretions or peripheral blood from CPPS/CP patients, and correlating with pelvic pain symptoms (32, 66-71). Remarkably, recently reported data indicates that a mast celldirected therapy improved the quality of life of CPPS/CP patients by alleviating pain and urinary symptoms in association with a downregulation of immune-related pathways including Th1 and Th17 T cell differentiation (72). From all these evidence, IFNgsecreting Th1 lymphocytes emerge as central drivers in the pathogenesis of the disease and the development of chronic pelvic pain, the characteristic symptom observed in CPPS/CP patients.…”
Section: Discussionmentioning
confidence: 91%
“…Once again, these findings mirror the human disease, since elevated levels of CCL2 and CCL3, the Th1-associated chemokine CXCL10, mast cellderived tryptase and other mediators, and significantly increased effector Th1/Th17 cell proportions have been found elevated in expressed prostatic secretions or peripheral blood from CPPS/CP patients, and correlating with pelvic pain symptoms (32, 66-71). Remarkably, recently reported data indicates that a mast celldirected therapy improved the quality of life of CPPS/CP patients by alleviating pain and urinary symptoms in association with a downregulation of immune-related pathways including Th1 and Th17 T cell differentiation (72). From all these evidence, IFNgsecreting Th1 lymphocytes emerge as central drivers in the pathogenesis of the disease and the development of chronic pelvic pain, the characteristic symptom observed in CPPS/CP patients.…”
Section: Discussionmentioning
confidence: 91%
“…An important and noteworthy aspect is that in the EAP model of CP/CPPS, both NOD/ShiLtJ and C57BL/6 mice develop pelvic tactile allodynia, albeit the C57BL/6 mice develop pelvic tactile allodynia to a lesser extent ( 13 , 14 , 37 ). In both the EAP and the CP1-induced mouse models of prostatitis, we have shown increased numbers and activity of mast cells in the prostate stroma ( 13 , 14 , 29 , 39 ). Furthermore, in the EAP model, we have observed an increase in PGP9.5 +ve neuronal structures in the stroma of the prostates ( 37 , 50 ).…”
Section: Discussionmentioning
confidence: 96%
“…To assess the presence of mast cells, we examined prostate sections to determine the numbers of mast cells in both C57BL/6 and NOD/ShiLtJ mice upon CP1 instillation. We and others have previously demonstrated that following bacterial instillation, inflammation and mast cell numbers are most pronounced in the dorsolateral lobe of the prostate (29,39,40). Dorsolateral prostate lobe sections from CP1-infected mice and control C57BL/6 and NOD/ShiLtJ mice were subjected to toluidine blue staining to assess increase of mast cell numbers.…”
Section: Cp1 E Coli Instillation In C57bl/6j and Nod/shiltj Mice Elevate Mast Cell Numbers In The Prostate But Produce Differential Effecmentioning
confidence: 99%